Student perceptions on high school teachers’ competence in online teaching - Dwiyanto Djoko Pranowo; Suwarna Dwijonagoro; Roswita Lumban Tobing; Sirima Purinthrapibal (Jurnal Cakrawala Pendidikan, 2023)
Efforts to continuously improve teacher competence need to be supported by the availability of empirical data through various studies. Data on teacher competence in Indonesia have so far been carried out by the government through the National Teacher Competency Test (NTCT) whose instruments were prepared based on indicators of professional teachers who master the competencies of the field of study and pedagogical competencies. The result was that most teachers in Indonesia did not pass the competency test. This article tries to describe user-based teacher competencies in this case, students. How students evaluate their teachers will be able to be a portrait from a different angle with NTCT. Through a questionnaire on student perceptions of teacher performance in online learning, it can provide an overview of the level of user satisfaction with teacher performance. The study involved 569 high school students from public and private schools, as well as urban and rural schools. The questionnaire was conducted through a google form and the results showed that according to student assessments, teachers were relatively ready to manage online learning. Passing the second year of online learning has been well addressed by teachers in improving self-competence. According to students, teachers are capable to use various technology platforms and media in virtual learning.